Visible Light Promoted, Catalyst-Free Radical Carbohydroxylation and Carboetherification under Mild Biomimetic Conditions - Altmann, Lisa-Marie; Zantop, Viviane; Wenisch, Pia; Diesendorf, Nina; Heinrich, Markus (Chemistry - A European Journal, 2021)
Metal and catalyst-free carbohydroxylations and carboetherifications at room temperature have been achieved by a combination of beneficial factors including high aryl diazonium concentration and visible light irradiation. The acceleration of the reaction by visible light irradiation is particularly remarkable against the background that neither the aryldiazonium salt nor the alkene show absorptions in the respective range of wavelength. These observations point to weak charge transfer interactions between diazonium salt and alkene, which are nevertheless able to considerably influence the reaction course. As highly promising perspective, many more aryldiazonium-based radical arylations might benefit from simple light irradiation without requiring a photocatalyst or particular additive.
CRIS-Team Scopus Importer:2021-02-05
Keywords: arylation; biomimetics; diazonium; Meerwein; styrene